GREEN ACCOUNTING ON ENVIRONMENTAL SUSTAINABILITY THROUGH WASTE MANAGEMENT IN MSMEs INDUSTRY CENTRE TAHU CIBUNTU - Maria Yulianti; Anne Lasminingrat; Hendrajat Setiadi (Faculty of Economic and Business, University of Pasundan, 2023)
The importance of environmental accounting basically requires complete knowledge of companies and other organizations that have benefited from the environment. Seeing this phenomenon is homework for all of us to take responsibility for providing solutions for MSME actors in the Cibuntu tofu industry center in Bandung Kulon District about the importance of environmental accounting for sustainability in waste management. The method used in this study is a mixed methods method. This research is a research step by combining two forms of research that have existed before, namely qualitative research and quantitative research. The result show that green accounting has a positive and significant effect on waste management. Waste management has a positive and significant effect on environmental sustainability. This shows that waste management can affect environmental sustainability in the Cibuntu Tofu Industry Center in Bandung Kulon District.